Directory of Approved Programs for the Preparation of Educational Personnel in Illinois Institutions of Higher Education. Volume 20 - Illinois State Board of Education, Springfield; Illinois State Board of Education, Springfield ([S.l.] : Distributed by ERIC Clearinghouse, 1996)
This twentieth edition of the Directory of Approved Programs has been updated to reflect the numerous changes in each recognized institution's approved program listing. The directory lists state approved programs for the preparation of education personnel in Illinois. Addresses, telephone numbers, and contact persons for each institution are listed. The data are provided in 11 sections: (1) alphabetical listing of recognized institutions and approved programs with listing of specific curriculum areas; (2) approved early childhood education certificate programs; (3) approved elementary (K-9) certificate programs; (4) approved secondary (6-12) certificate program areas; (5) approved special (K-12) certificate program areas; (6) approved special education areas for the special (K-12) certificate; (7) approved school service personnel certificate programs; (8) approved administrative credit certificate programs; (9) approved transitional bilingual certificate programs; (10) geographic location of Illinois institutions recognized for teacher education; and (11) special programs offering alternatives for individuals with degrees. (JLS)
ERIC Note: For previous directory, see ED 267 058.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Bilingual Education; Educational Certificates; Elementary Secondary Education; Higher Education; Preservice Teacher Education; School Personnel; Special Education; Teacher Certification; Teacher Education Programs; Teachers; Illinois; Reference Materials, Directories/Catalogs.